Accurate Triage of Oncological Patients for Safely Continuing Cancer Therapy During the SARS-CoV-2 Pandemic - Gurizzan, Cristina; Pedersini, Rebecca; Fornaro, Carla; Sardini, Chiara; Zamparini, Manuel; Monteverdi, Sara; Tovazzi, Valeria; Cosentini, Deborah; Dalla Volta, Alberto; Baggi, Alice; Turla, Antonella; Di Mauro, Pierluigi; et al. (Frontiers in Oncology, 2021)
Objective: To evaluate the efficacy of clinical triage of oncological patients for safe continuation of cancer therapy implemented during the first SARS-CoV-2 outbreak. Methods: Between 25 February and 21 April 2020, patients attending the Medical Oncology Unit, Spedali Civili Hospital, Brescia (Italy) for cancer therapy underwent triage to identify those with no signs and symptoms suspicious for SARS-CoV-2 infection in which antineoplastic treatment could be continued as scheduled. Triage questions investigated common symptoms (e.g., fever, cough, dyspnea, anosmia, dysgeusia, headache, nasal congestion, conjunctival congestion, sore throat, diarrhea, nausea and vomiting); body temperature and pulse oximetry were also recorded. All patients were followed-up for overt SARS-CoV-2 through to 18th May 2020. Results: Overall, 1180 patients (median age 65 years) underwent triage during the study period. The most frequent primary malignances were breast (32%), gastrointestinal (18%), and lung (16.5%) cancer. Thirty-one (2.5%) presented with clinically evident SARS-CoV-2 infection and tested positive on nasopharyngeal swab testing and/or radiological imaging. Triage identified 69 (6%) grey zone patients with symptoms suspicious for SARS-CoV-2; 5 (7.2%) subsequently developed symptomatic disease. Neither the symptomatic nor the grey zone patients received their scheduled treatment; instead, they were referred for hospitalization or home quarantine. Conclusion: Triage of oncological patients at our Unit provided for safe continuation of scheduled cancer treatment in 91.5% of patients during the initial SARS-CoV-2 outbreak.